The application of DNA technology for genetic testing of athletes - Rogozkin, V.; Ahmetov, I.; Astratenkova, I.; Druzhevskaya, A.; Komkova, A. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Genetic testing is a complex process that utilizes multiple laboratory techniques to analyze human DNA, RNA, proteins and metabolites. Testing of genetic variants can serve diverse purposes, including diagnostic testing, identification of future health risk, prediction of drug responses, and formation, development and manifestation of physical qualities of elite athletes [1]. Understanding of genetic variability can shed light on commonly encountered situations and can contribute to a better understanding of the relationship between human and exercise, performance and physical activity [2,3]. The elite athlete is probably an individual with a favorable profile in terms of the morphological, physiological, metabolic, biochemical and personality determinants of the relevant sport. The elite athlete is a highly responsive individual to regulate training and practice. The evidence for a role of genes in modulating the status of performance determinants in a sedentary population is slowly accumulating. The search for genetic markers of trainability status will likely be more productive than the investigation of molecular markers of the performance phenotype on the untrained state. The purpose of this study was to determine genotype and allele frequencies of 18 genes in elite athletes and to detect genotype combinations that are prevalent in elite and sub-elite athletes compared to controls. 1.305 male and female Russian athletes of regional or national competitive standard were recruited from 22 summer and winter Olympic sports. The athletes were prospectively stratified into groups according to event duration and distance covering a spectrum from the more endurance-oriented to the more poweroriented. Controls consisted of 1.242 healthy subjects, aged 13-42. ACE, ACTN3, AMPD1, AR, CNB, HIF1A, MYF6, NFATC4, NOS3, PPARA, PPARD, PPARG, PGC1A, PGC1B, TFAM, VEGF, UCP2, UCP3 gene polymorphisms were determined by PCR-RLFP. We found that the frequencies of ACE I, AMPD1 C, MYF6 T, NOS3 5, PPARA G, PPARD C, PGC1A Gly, VEGF C alleles were significantly higher in endurance-oriented elite athletes than in controls, whilst the frequency of ACE D, ACTN3 R, MYF6 C, PPARA C, PPARG Ala alleles were overrepresented in power-oriented athletes. We revealed the stronger association of gene variants with elite athletic performance when alleles with the same effect were combined. Moreover, we found unique genotype combinations which were linked to specific kinds of sports. In conclusion, the discovered interrelation between gene variants and athletic performance was found mainly with the use of combinatorial approach, confirming the phenomenon of multiple character of human physical traits hereditability.